The Correlation Between Students' Reading Ability And Their Vocabulary Mastery at Eighth Grade of SMP Darul Falah Kemang Indah - Sri Indrasanti Ghanie (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading is one of the activities that students can use to expand their knowledge and strengthen their critical thinking skills, and one of the most essential components of reading is vocabulary mastery. In this case, both vocabulary and reading cannot be separated. So, this research aimed to find the correlation between students’ reading ability and their vocabulary mastery.In this research, the researcher used quantitative approach, to measure the correlation between two variables; vocabulary mastery (X) and reading ability (Y), the researcher used a Pearson Product Moment Correlation. The researcher analyzed it by using the statistic software Statistical Product and Service Solution (SPSS) 16. In this research the researcher using a test. The test consisted of 40 multiple choice questions that were divided into two parts. Twenty questions are for vocabulary and twenty questions are for reading. The subject of this research is 37 students at eighth grade of SMP Darul Falah in the academic year 2021/2022.From the calculation, it was found that the mean for vocabulary mastery was 51.62 and the standard deviation was 17.797, while the mean for reading was 53.65 and the standard deviation was 14.026. The significant value was 0.000, which is less than 0.05. Further, the r-value is 0.766 based on the table correlation coefficient, which means there was high and positive correlation between the two variables. So, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Based on the results of the research, it can be concluded that there is a positive correlation between vocabulary mastery and the reading ability of eighth grade students of SMP Darul Falah Kemang Indah. This correlation includes a high correlation based on the degree of correlation.Finally, because there are some limitations to this research, it is highly recommended for future researchers to carry out a deeper analysis, and it is hoped that future researchers will use more populations and samples in their research. In addition, this research also serves as feedback to English teachers to evaluate their teaching performance especially in using vocabulary and reading, so that vocabulary mastery and reading ability are always connected.Key Words: Correlation, reading ability, vocabulary mastery